A Descriptive Analysis of Integrated Plastic Surgery Residency Program Directors in the United States. Issue 4 (7th June 2022) - Hughes, Alexa J.; Samson, Thomas D.; Henry, Cathy R.; Johnson, Timothy Shane
Abstract : Background: The role sex plays in surgical leadership positions is heavily discussed in the literature; however, there is an absence of research looking at plastic surgery program director (PD) demographics and the differences between male and female PDs. Methods: A cross sectional study of publicly available online resources of all integrated plastic surgery residency programs was performed. Demographic and academic data of integrated plastic surgery PDs was analyzed focusing on the differences in PDs based on sex. Results: Eighty-two integrated plastic surgery residencies were analyzed. Fifteen PDs (18.3%) were female. Fifty-six (68%) PDs completed general surgery residencies, whereas 24 (29%) completed an integrated plastics residency. All female PDs were fellowship trained, whereas only 46 (68%) male PDs pursued additional training after residency ( P = 0.02). Research output among male PDs was greater with 49.9 publications and a higher average H-index, at 13.3, compared with women with an average of 27.5 publications ( P = 0.008) and an H-index of 8.7 ( P = 0.02). When comparing male to female PDs, there was no difference between age at PD appointment ( P = 0.15), or in the amount of time between completion of plastic surgery training to PD appointment ( P = 0.29). Male PDs were older (52.2) compared with female PDs (46.5) ( P = 0.02). Male PDs served longer terms (4.98 years) than female PDs (2.87 years) ( P = 0.003). Conclusions: The majority of integrated plastic surgery PDs are men with a Doctor of Medicine degree who completed a general surgery residency and a plastic surgery fellowship. Most PDs also completed fellowship in a plastic subspecialty. Male PDs had higher research output, which may be attributed to their older age on average. Although women make up only 18.3% of plastic surgery PDs, this percentage is similar to the 17.2% of active female plastic surgeons in the United States. As more women train in plastic surgery, it is possible that the percentage of women serving academic leadership roles will increase. By gaining a better understanding of the demographics and diversity in plastic surgery residency program leadership, efforts can be made to increase the representation of minority groups in academic leadership roles.